PTH-109 Management Of Bile Acid Malabsorption (bam) With Low Fat Dietary Interventions. (9th June 2014) - Watson, L; Lalji, A; Bodla, S; Andreyev, J; Shaw, C
Abstract : Introduction: BAM is the unrecognised cause for loose stool for 500, 000 people in the UK. It is increasingly recognised as a potential cause of distressing gastrointestinal (GI) symptoms after cancer treatment. This study aims to evaluate the efficacy of low fat dietary interventions in the management of BAM. Methods: Patients with new onset GI symptoms after cancer treatment and a 7 day 23-selena-25-homochololytaurine (SeHCAT) scan <20%, were included in a prospective service evaluation. Patients were advised on a low fat dietary intervention by a Registered Dietitian, which aimed to provide 20% of total energy from fat. Patients rated their GI symptoms using a 10 point numerical rating scale, and completed 7 day dietary diaries, before and after dietary intervention. The dietary diaries were analysed using the dietplan6 dietary analysis programme. Significance of changes in symptom scores were analysed using Wilcoxon signed-ranks test, change in dietary fat intake using a paired t-test. Results: 40 patients (20 male, 20 female) with a median age 61 (range 22–90) years were recruited. The cancer diagnoses were GI (28%), gynaecological (30%), urological (30%) and other (12%). 7.5% had borderline BAM (15–20% 7 day retention), 25% mild BAM (10–15% retention), 17.5% moderate (5–10% retention) and 50% severe (<5% retention). 62.5% of patients were taking a bile acid sequestrant. Symptoms reported were urgency (83%), bloating (43%), increased frequency (43%), lack of control (40%), abdominal pain (38%), nocturnal defaecation (28%), incomplete evacuation (25%) and greasy/pale stools (23%). After dietary intervention, the mean scores for all symptoms decreased. There was a significant reduction in mean ratings for urgency, bloating, lack of control, bowel frequency (p = <0.01), flatulence, abdominal pain, greasy/pale stool and abdominal gurgling (p = <0.05). Mean dietary fat intake reduced from 62.3 g of fat before dietary intervention to 42.2 g of fat after intervention (p = <0.01). There was no statistically significant change in dietary fibre intake. Conclusion: The use of low fat dietary interventions in patients with a SeHCAT scan <20% leads to clinically important improvement in GI symptoms and should be widely used. Disclosure of Interest: None Declared.